2003
DOI: 10.1002/chin.200323147
|View full text |Cite
|
Sign up to set email alerts
|

Azacycloalkanes. Part 34. Synthesis and Antiarrhythmic Activity of 2‐(2′‐R‐2′‐Hydroxyethyl)‐1,2,3,4‐tetrahydropyrrolo[1,2‐a]pyrazines.

Abstract: Pyrazine derivatives Pyrazine derivatives R 0550Azacycloalkanes. Part 34. Synthesis and Antiarrhythmic Activity of 2-(2'-R-2'-Hydroxyethyl)-1,2,3,4-tetrahydropyrrolo[1,2-a]pyrazines. -A variety of novel title hydroxyethyl-substituted tetrahydropyrrolopyrazines (III) are prepared as demonstrated for derivative (IIIa) and isolated as fumarate salts. Among them, derivatives (IIIa) and (IIIc) possess the highest antiarrhythmic activity. -(LIKHOSHERSTOV, A. M.; FILIPPOVA, O. V.; PERESADA*, V. P.; KRYZHANOVSKII, S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…
New procedures have been developed for the synthesis of α-(2-formyl-1H-pyrrol-1-yl)-substituted carboxylic acids, α-(2-R-aminomethyl-1H-pyrrol-1-yl)-substituted carboxylic acids, and 1,2-dihydropyrrolo-[1,2-a]pyrazin-3(4H)-ones on the basis of furfurol and α-amino acids.* For communication XXVIII, see [1].We previously described methods for the synthesis of a series of 1,2-substituted pyrroles [2] and 3,4-dihydropyrrolo[1,2-a]pyrazines [3,4] and showed that some of these compounds exhibit cardiovascular [2] and psychotropic [5] activity. It is also known that the process of preparing food by heating is accompanied by formation of various pyrrole and pyrrolo[1,2-a]pyrazine derivatives from carbohydrates and proteins [6,7], and these compounds are introduced into human organism together with food.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
New procedures have been developed for the synthesis of α-(2-formyl-1H-pyrrol-1-yl)-substituted carboxylic acids, α-(2-R-aminomethyl-1H-pyrrol-1-yl)-substituted carboxylic acids, and 1,2-dihydropyrrolo-[1,2-a]pyrazin-3(4H)-ones on the basis of furfurol and α-amino acids.* For communication XXVIII, see [1].We previously described methods for the synthesis of a series of 1,2-substituted pyrroles [2] and 3,4-dihydropyrrolo[1,2-a]pyrazines [3,4] and showed that some of these compounds exhibit cardiovascular [2] and psychotropic [5] activity. It is also known that the process of preparing food by heating is accompanied by formation of various pyrrole and pyrrolo[1,2-a]pyrazine derivatives from carbohydrates and proteins [6,7], and these compounds are introduced into human organism together with food.
…”
mentioning
confidence: 99%
“…We previously described methods for the synthesis of a series of 1,2-substituted pyrroles [2] and 3,4-dihydropyrrolo[1,2-a]pyrazines [3,4] and showed that some of these compounds exhibit cardiovascular [2] and psychotropic [5] activity. It is also known that the process of preparing food by heating is accompanied by formation of various pyrrole and pyrrolo[1,2-a]pyrazine derivatives from carbohydrates and proteins [6,7], and these compounds are introduced into human organism together with food.…”
mentioning
confidence: 99%